Degradation of PCDD/Fs from incineration of waste at low temperatures for resource utilization of fly ash - Songxuan CHEN; Hao WANG; Dongwei ZHANG; Mengxiao LAN; Zhi SUN; Yuping GAO; Hongbin CAO (Scientific Reports, 2025)
Abstract Municipal solid waste incineration fly ash (MSWIFA) is of great value in resource utilization. Harmless pretreatment is a crucial prerequisite for the resource utilization of MSWIFA. The detoxification process is a crucial step in the harmless pretreatment of MSWIFA. This includes polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs), which are among the most toxic substances to humans and other living organisms. Low-temperature degradation technology has broad prospects in engineering applications due to the advantages of low technical difficulty and operating costs. This work conducts a pilot test on the degradation of 17 toxic PCDD/Fs in MSWIFA at low temperatures. The pilot test investigates the effects of reaction temperature and oxygen content on the degradation of PCDD/Fs in MSWIFA. Furthermore, based on the perspective of MSWIFA resource utilization, an analysis and a proposal are made to judge the degradation effect of low-temperature thermal treatment technology on PCDD/Fs in MSWIFA. Further, taking the soil sludge field as the application scenario, the application feasibility of MSWIFA after detoxification is analyzed. The flotation process markedly reduces both the carbon content and the levels of PCDD/Fs in MSWIFA. The hydrothermal method facilitates the degradation of dioxins in fly ash while introducing oxygen significantly lowers the reaction temperature required for fly ash treatment. This can enhance the degradation rate and reduce the demands on reaction equipment. The results indicate that the low-temperature thermal treatment technology can effectively degrade PCDD/Fs in MSWIFA, satisfying the requirements of some application scenarios. Notably, evaluating the effect of low-temperature thermal treatment technology on the degradation and detoxification of PCDD/Fs in MSWIFA should satisfy the residue requirements of different industries and achieve a certain detoxication efficiency.